THE INCLINATION OF COASTLINE CHANGES AND ITS IMPLICATION FOR LANDUSE MANAGEMENT OF KARAWANG DISTRICT, WEST JAWA PROVINCE - Ediar Usman (Marine Geological Institute of Indonesia, 2009)
Result of observation at 11 locations and the coastline analysis at year map 1990 published by Bakosurtanal and year map 2005 published by Bappeda of Karawang District shows that the existence of changes of the coastline is caused by abrasion and accretion process. The coastal abrasions are occurred in Muarabaru, South Pusakajaya, Cemarajaya and Tanjungpakis areas. The coastal accretions are occurred in Ciparage - Sukajaya, Mekarpohaci, Cemarajaya - South Pusakajaya, East and West Tanjungpakis areas. During the periods of 15 years the abrasions are occurred with the width of 813,171 ha (8,13171 km2) and the coastal long of 30,637 km, and accretions with the width of 1346,22 ha (13,4622 km2) and the coastal long of 43,313 km. Every year the width of abrasion is about 54,21 ha or about 0,5421 km2/year and the width of accretion is about 89,748 ha/year or 0,8975 km2/year. The growth of coastal area about 89,748 ha/year or 0,8975 km2/year. If the coastal management is conducted at the abrasion coasts, the coastal damage can be decreased, and the coastal growth for the productive landuse can be increased. Keywords: coastline changes, abrasion, accretion, landuse development. Hasil pengamatan pada 11 lokasi dan analisis garis pantai pada peta tahun 1990 yang dipublikasikan oleh Bakosurtanal dan peta tahun 2005 yang dipublikasikan oleh Bappeda Kabupaten Karawang menunjukkan adanya perubahan garis pantai yang disebabkan oleh proses abrasi dan akresi. Pantai abrasi terjadi di daerah Muarabaru, Pusakajaya Selatan, Cemarajaya, Sedari dan Tanjungpakis. Pantai akresi terjadi di daerah Ciparage - Sukajaya, Mekarpohaci, Cemarajaya - Pusakajaya Selatan dan Tanjungpakis Timur & Barat Selama kurun 15 tahun telah terjadi abrasi seluas 813,171 ha (8,13171 km2) dengan panjang pantai 30,637 km, dan akresi seluas 1346,22 ha (13,4622 km2) dengan panjang pantai 43,313 km. Setiap tahun terjadi abrasi seluas 54,21 ha atau sekitar 0,5421 km2/tahun dan akresi seluas 89,748 ha/tahun atau sekitar 0,8975 km2/tahun. Pertumbuhan kawasan pantai masih lebih besar, yaitu sekitar 89,748 ha/tahun atau sekitar 0,8975 km2/tahun. Bila pengelolaan dilakukan pada pantai-pantai abrasi, maka kerusakan pantai dapat dikurangi dan pertumbuhan pantai untuk lahan produktif masih dapat ditingkatkan. Kata kunci: perubahan garis pantai, abrasi, akresi, pengembangan tataguna lahan.